Rapid and specific detection of Enterococcus faecalis with a visualized isothermal amplification method - Zhu, Bo; Hu, Juan; Li, Xuelian; Li, Xiaomin; Wang, Lei; Fan, Shihui; Jin, Xin; Wang, Kun; Zhao, Weiguo; Zhu, Wenjun; Chen, Cheng; Wang, Zilu; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Enterococcus faecalis is a serious problem for hospitals and can spread from patient to patient. Most of the current detection methods are associated with limitations associated with the need for trained personnel; they are also time-consuming. Thus, it is necessary to develop rapid and accurate detection methods to control the spread of E. faecalis. In this study, we developed a rapid and accurate detection method for E. faecalis using recombinase polymerase amplification (RPA) combined with a lateral flow strip (LFS). This method could be completed in approximately 35 min at 37°C. The limit of detection was 10 CFU/µL, irrespective of whether the templates were pure or complex. This method also showed good specificity and compatibility. In total, 278 clinical samples were tested using the RPA-LFS method; the detection accuracy was equal to that of the conventional qPCR method. This visualized isothermal amplification method could be useful for the future on-site detection of E. faecalis.